Evaluation and Management of Misophonia Using a Hybrid Telecare Approach: A Case Report - Zitelli, Lori (Seminars in Hearing, 2021)
Decreased sound tolerance (DST) is a negative reaction to environmental sounds and is estimated to affect 3.5% of the population. This case report presents the evaluation and management of an adult female with severe, longstanding misophonia. Her evaluation included comprehensive audiometric testing (including uncomfortable loudness levels) and a detailed assessment of the impact of DST on her life. She enrolled in tinnitus retraining therapy and began receiving treatment aiming to facilitate habituation of bothersome environmental sounds. This case was complicated by the advent of the coronavirus disease 2019 (COVID-19) pandemic and a telemedicine hybrid approach was employed to increase access to audiologic care. Using this structure, some appointments occurred in person in the clinic and others occurred via a telemedicine video visit format. Telemedicine video visits facilitated in-depth discussions, afforded the opportunity to answer questions, and provided the option of cloud-based remote programming of on-ear devices. Future care will continue to employ a hybrid approach.
Keywords: misophonia; decreased sound tolerance; hybrid telemedicine; tinnitus retraining therapy